Narrative of Nationalism in The Indonesian High School History Textbooks For Grade XI - Guchi, Muslim; Handoko, Satrio Awal (Sebelas Maret University (UNS), 2019)
This study aims to analyze the inculcation of nationalism in Indonesian History textbooks at Class XI High School. The problems raised are: (1) How did the rise of Indonesian nationalism begin? (2) How was revolutionary nationalism in Indonesia? The research method used is content analysis, which is analyzing the content of textbooks on Indonesian history. The approach used is Arnold Joseph Toynbee's theory of